Implementasi Program Desa Berdaya Melalui Economic Branding Pada Dinas Pemberdayaan Masyarakat dan Desa Kabupaten Lamongan - Riska Ayu Lestary; Krishno Hadi; Ach. Apriyanto Romadhan (Asosiasi Ilmuwan Administrasi Negara (ASIAN), 2022)
This study examined the Program Desa Berdaya which is a form of the East Java Provincial Government with the aim to help improve the economy of rural communities in East Java, it is the impact of the Covid-19 pandemic. In this paper uses policy implementation theory that analyzes the Empowered Village program with 4 variables, namely: (1) Analysis of Policy Content Between Policy Levels (2) Institutions and Policy Implementing Resources (3) Program Socialization (4) Program Target Group Response. This research uses qualitative methods through descriptive approaches with data collection techniques through observation, documentation, and interviews. This research was conducted for 2 months at the Lamongan Regency Community and Village Empowerment Office. The results of the study showed that this program provides assistance to villages to realize products that will become village icons, the involvement of local governments ranging from provinces, districts/cities to villages is very influential on the success of the Empowered Village Program. In its implementation, of course, there are several mechanisms that are carried out. The realization of the Empowered Village program went well because the village had implemented several indicators of success that had been set out in the program guidelines.